Functionalization of cellulose as imprinted adsorbent for selective adsorption of matrine. Issue 8 (12th August 2019) - Qiu, Yueming; Lin, Chunxiang; Liu, Yifan; Lv, Yuancai; Liu, Minghua
ABSTRACT: A novel molecular imprinted polymer (MIP) based on cellulose is fabricated for separation of matrine. Cellulose graft copolymer was first synthesized from cotton linter by atom transfer radical polymerization in ionic liquid with the acrylamide as monomer. Then, the prepared graft copolymer underwent sulfomethylation and subsequent crosslinking in the matrine solution. Effects of the parameters on the reaction degree were discussed, and the structural, component, and morphological characterization of the products were also conducted. The ability of the obtained cellulose‐based MIP (MIP‐SPAM) to adsorb matrine was evaluated by batch adsorption. Results showed that the sorption process was pH dependent, spontaneous, endothermic, and followed the Langmuir adsorption isotherm. Kinetics study revealed that pseudo‐second‐order was closed to the experimental data and both of the membrane diffusion and intraparticle diffusion controlled the matrine adsorption. Moreover, MIP‐SPAM possessed higher selective sorption property for matrine compared to the corresponding nonimprinted polymer. Finally, the MIP‐SPAM could be repeatedly used for five times without any significant loss in the initial binding affinity. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48392. Abstract : Synthesis route of cellulose supported MIP